Acquired KRAS mutation and loss of low-level MET amplification after durable response to crizotinib in a patient with lung adenocarcinoma. (July 2019) - Riedel, Richard; Michels, Sebastian; Heydt, Carina; Siemanowski, Janna; Kobe, Carsten; Bunck, Anne; Schäfer, Stephan; Fischer, Rieke N.; Scheffler, Matthias; Abdulla, Diana S.Y.; Nogová, Lucia; Koleczko, Sophia; et al.
Highlights: A patient with low-level MET amplification and high MET expression showed response to treatment with crizotinib. Resistance was associated with loss of MET amplification and acquired KRAS mutation. This points to the limitations of defining cut-offs for continuous biomarkers. Abstract: Objectives: Resistance to tyrosine kinase inhibitor (TKI) therapy occurs inevitably in lung cancer patients with targetable genetic alterations. MET amplification has found to be an oncogenic driver in lung cancer with several reports showing response to MET TKI especially in cases with high-level amplification. Materials and methods: We report the case of a patient with lung adenocarcinoma harbouring low-level MET amplification and strong MET expression who was treated with crizotinib. Results: The patient developed a durable response to crizotinib. A KRAS mutation and loss of MET amplification was found in a new lesion at time of progression as a potential mechanism of acquired resistance. Conclusion: MET amplification is a continuous biomarker with responses to MET TKI observed even in patients with low-level amplification. KRAS mutations may act as a resistance mechanism to MET inhibition in MET dependent lung cancer.